Characteristics, trends, outcomes, and costs of stimulant-related acute heart failure hospitalizations in the United States. (15th May 2021) - Shetty, Suchith; Malik, Aaqib H.; Ali, Abbas; Yang, Ying Chi; Briasoulis, Alexandros; Alvarez, Paulino
Abstract: Background: Heart failure (HF) hospitalizations remains a significant burden on the health care system. Stimulants including cocaine, amphetamine and its derivatives are amongst the most used illegal substances in the United States. The information regarding stimulant-related HF hospitalizations is scarce. We sought to evaluate the characteristics and trends of stimulant-related HF hospitalizations in the United States and their associated outcomes and resource utilization. Methods: Using the National Inpatient Sample (NIS), we identified patients with a primary diagnosis of HF hospitalization. These hospitalizations were further divided into those with and without a concomitant diagnosis of stimulant (cocaine or amphetamine) dependence or abuse. Survey specific techniques were employed to compare trends in baseline characteristics, complications, procedures, outcomes and resource utilization between the two cohorts. Results: We identified 9, 932, 753 hospitalizations (weighted) with a primary diagnosis of heart failure, of those 138, 438 (1.39%) had a diagnosis of active stimulant use. The proportion of stimulant-related HF hospitalization is on the rise (1.1% to 1.9%). Stimulant-related HF hospitalization was highest amongst age group 30–39 years and 7.9% of HF hospitalizations in this age group were due to stimulant use. The proportion of stimulant-related HF hospitalization for the White and Hispanic race has doubled from 2008 to 2017. Stimulant-related HF hospitalization is associated with increased incidence of in-hospital complications like cardiogenic shock, acute kidney injury and ventricular tachycardia. These patients have more than 7-fold higher discharge against medical advice. Conclusions: Stimulant-related HF hospitalizations have been increasing. It is associate with significant morbidity burden and health care utilization. Highlights: Stimulant related acute congestive heart failure hospitalization (ACHF) is currently on the rise in the United States. Stimulant related ACHF hospitalization peaks at age 30–39 years and accounts for 8% of heart failure hospitalization from all cause. Stimulant related ACHF hospitalization mostly affects African Americans, however there is a steady yet gradual trend of increased hospitalization in other race groups. The proportion of stimulant related hospitalization for Whites and Hispanics has doubled between 2008 and 17. Stimulant related ACHF hospitalizations had a > 7-fold higher discharge AMA.